2010
DOI: 10.1016/j.ejpain.2009.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Differential physiological effects during tonic painful hand immersion tests using hot and ice water

Abstract: a b s t r a c tThe cold pressor test (CPT) is an empirically validated test commonly used in research on stress, pain and cardiovascular reactivity. Surprisingly, the equivalent test with water heated to noxious temperatures (hot water immersion test, HIT) has not been thoroughly investigated. The aim of the present study was to characterize the physiological effects and psychophysics of both tests and to analyze whether the autonomic responses are mainly induced by baroreflexes or a consequence of the pain ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
56
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 33 publications
12
56
0
4
Order By: Relevance
“…The observed effects of stress on the CMS may be specific for the CP intervention. The CP test elicits vascular constriction, which is specific for cold water exposure (Streff et al, 2010) and is also indicated in our data by the reduction of pulse transit time. Venous pooling caused by the CP test (Brod et al, 1979) and, therefore, increased central venous pressure, may play a key role in the observed early effect on the CMS.…”
Section: Discussionsupporting
confidence: 82%
“…The observed effects of stress on the CMS may be specific for the CP intervention. The CP test elicits vascular constriction, which is specific for cold water exposure (Streff et al, 2010) and is also indicated in our data by the reduction of pulse transit time. Venous pooling caused by the CP test (Brod et al, 1979) and, therefore, increased central venous pressure, may play a key role in the observed early effect on the CMS.…”
Section: Discussionsupporting
confidence: 82%
“…This task is similar to cold pressor testing in terms of eliciting a pain response. Hot water was chosen to avoid the possibility of prompting a vaso-occlusive crisis and avoids baroreflex activation [48]. Participants immersed the dominant hand in a circulating water bath maintained at a tailored temperature designed to be moderately painful.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies expose the skin to radiant heat [16], heated water [17], or extreme cold (e.g., the cold pressor test) [18]. Other studies generate ischemic pain by obstructing blood flow in an extremity, as occurs when a blood pressure cuff is inflated [19].…”
Section: Research In Psychology and Behavioral Sciencesmentioning
confidence: 99%